HOTS-BASED LEARNING EVALUATION DESIGN TO IMPROVE EARLY SCHOOL LEARNING - Andiono, Nurkilat (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2024)
The quality of education in Indonesia today is very worrying. The poor quality of Indonesian education can be seen from the low quality of Indonesia's education and the low learning performance. The learning outcome is a measure in determining the success of a learning. Research on learning evaluation through HOTS (High Order Thinking Skills) is becoming more relevant and urgent to explore. Therefore, this study aims to describe the HOTS-based learning evaluation design to improve student learning outcomes. In order to obtain data from the research results, research is carried out with a qualitative approach and type of case study. The research was conducted at MI Raudlatul Ulum Jabung Wetan Paiton Probolinggo, from November-December 2023. Data collection techniques with participant observations, in-depth interviews and documentation. While data analysis techniques using the Miles Huberman model include data collection, data reduction, data display and conclusion withdrawal. The results of this research show that the design of HOTS-based learning evaluation in improving the learning outcomes of SKI at MI Raudlatul Ulum Jabung Wetan Paiton Probolinggo are: Graduate Competence Standards Training, HOTS Based Learning Evaluation Training, Hots Based Examination Questions Training and Evaluating Monitoring.